2020
DOI: 10.1016/j.ecoenv.2020.111068
|View full text |Cite
|
Sign up to set email alerts
|

Identification of receptors for eight endocrine disrupting chemicals and their underlying mechanisms using zebrafish as a model organism

Abstract: Herein, eight common endocrine disrupting chemicals (EDCs) were exposed to zebrafish (Danio rerio) to investigate the relationship between different EDCs and their activated estrogen receptors. Under acute exposure, we identified five major malformation types whose incidence and deformity modes differed among EDCs. Luciferase analysis divided the EDC receptors into four categories: (i) triclosan (TCS), 17ß-estradiol (E2) and estriol (E3) mainly activated GPER expression; (ii) bisphenol A (BPA), p-(tert-octyl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In recent years, research on TCS and its metabolite triclocarban (TCC) has mainly focused on the ecological environment and aquatic organisms 2,36,37 . Many studies have also confirmed a range of potential hazards of TCS, such as genetic toxicity, endocrine disruption, cardiac toxicity, neurotoxicity, and adverse pregnancy outcome 38–42 . In particular, the neurotoxicity induced by TCS has gradually become the focus of research due to its unclear mechanism of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on TCS and its metabolite triclocarban (TCC) has mainly focused on the ecological environment and aquatic organisms 2,36,37 . Many studies have also confirmed a range of potential hazards of TCS, such as genetic toxicity, endocrine disruption, cardiac toxicity, neurotoxicity, and adverse pregnancy outcome 38–42 . In particular, the neurotoxicity induced by TCS has gradually become the focus of research due to its unclear mechanism of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…(Li et al, 2020;Zhu et al, 2020). Thus, we posit that TCS targets GPER for activation of the PKC/MAPK signaling pathway, in which PKC is phosphorylated to become dissociated from the PKC-Keap1 compound and thereby becomes activated (Huang et al, 2020). MAPK is mainly composed of four sub-families, which are extracellular signal-regulated kinase (ERK), p38 mitogen-activated protein kinase (p38 MAPK), c-Jun N-terminal kinase (JNK) and extracellular signal-regulated kinase 5 (ERK5) (Dou et al, 2021).…”
Section: Activation Of the Pkc/mapk Pathway Triggers Mir-144 Upregula...mentioning
confidence: 98%
“…In recent years, TCS was documented to have an estrogenic effect through targeting a new type of G-protein coupled estrogen membrane receptor (GPER) (Wang et al, 2021). Previous research by our group documented that TCS exposure activated GPER to trigger an estrogen effect (Huang et al, 2020). GPER is a non-classical estrogen receptor binding to the plasma membrane through seven transmembrane domains, it is widely distributed in the brain functional area related to emotion control, serving an important role in regulation of the HPA axis and mood (Zheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPR30 plays a key role in the physiology of the reproductive system [ 16 , 17 ] and metabolism [ 18 ]. In the case of BPA, it has been shown to bind to multiple ERs including ERα, ERβ (cytoplasmic and membrane-bound), GPR30 and human nuclear receptor estrogen-related receptor gamma (ERRγ) [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%